Analyzing the Implementation of Public Relations Ethics at PT KAI and Its Implications on Competitive Advantage - Lisdiantini, Netty; Zubair, Feliza; Perbawasari, Susie; Baruno, Agustiawan Djoko; Radjamin, Irzameingindra Putri (PT. Banjarese Pacific Indonesia, 2025)
This study examines the role of public relations (PR) ethics in enhancing PT Kereta Api Indonesia's (PT KAI) competitive advantage in the railway industry. Ethical practices in PR are vital for fostering stakeholder trust, improving customer satisfaction, and enhancing employee engagement, all of which contribute to sustainable growth and market leadership. Adopting a qualitative research design and a case study approach, the research investigates how ethical principles such as transparency, integrity, equity, respect, and responsiveness are applied within PT KAI’s operational and strategic frameworks. Data collection involved document and thematic analyses, emphasizing ethical practices’ impact on stakeholder relationships and competitive outcomes. The findings highlight that PT KAI’s ethical initiatives strengthen its reputation, promote customer loyalty, and support a positive workplace environment. Despite these successes, challenges remain, including the absence of formalized ethical guidelines and the need for ethical leadership. The study concludes that integrating PR ethics into organizational culture enhances competitive advantage and ensures long-term sustainability in a dynamic market.